Implementation of the Independent Curriculum in Science Learning in Class III of MIN Kota Jambi - Elsa Ramadhani; M. Syahran; Paujan Azim (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The implementation of the Independent Curriculum in science and science learning in class III MIN Jambi City is important to study because curriculum changes require learning that is more flexible, contextual and student-centered, but in the field there are still various obstacles in its implementation. This research aims to describe the implementation of the Merdeka Curriculum in science and science learning and identify the obstacles faced by third grade teachers. The research used a qualitative approach with a case study design, through data collection stages in the form of observation, in-depth interviews, and documentation, with the subjects being school principals, class III teachers, and class III students at MIN Jambi City. The research results show that science and science learning refers to the Merdeka Curriculum learning achievements and is carried out through observation, discussion, simple experiments and small projects that encourage student activity. However, implementation has not been optimal due to limited teacher understanding, lack of learning resources and teaching tools, limited facilities, and variations in student readiness. These findings confirm that successful implementation of the Independent Curriculum requires strengthening teacher capacity, school support, and providing adequate learning media.